Bugeye Lakes Complex Water Level Sensor Data, Arctic Coastal Plain of northern Alaska, 2021-2022 ... - Jones, Benjamin (NSF Arctic Data Center, 2023)
Taken together, lakes and drained lake basins may cover up to 80% of the lowland landscapes in permafrost regions of the Arctic. Lake formation, growth, and drainage in lowland permafrost regions create a terrestrial and aquatic landscape mosaic of importance to geomorphic and hydrologic processes, tundra vegetation communities, permafrost and ground-ice characteristics, biogeochemical cycling, wildlife habitat, and human land-use activities. Our project focuses on quantifying the role of thermokarst lake expansion, drainage, and drained lake basin evolution in the Arctic System. We did this through a combination of field studies, environmental sensor networks, remote sensing, and modeling. This dataset consists of environmental sensor records that record temperature and water level at three lakes in the Bugeye Lakes Complex in 2021 and 2022. Onset HOBO water level loggers (U2OL-04) were deployed in Bugeye Lakes 1, 2, and 4 in 2021 and 2022 to record temperature and pressure changes at 30-minute intervals. ...